CRIMINAL ACTS RELATED TO GENERAL ELECTIONS PURSUANT TO LAW NUMBER 10 YEAR 2008 - Moch. Ali Bachri (Jurnal IUS Kajian Hukum dan Keadilan, 2013)
The existence of criminal acts regulation in a Law surely purposed to the obedience of the people to the norms available in the law. However if it took a massive portion, the criminal acts regulation of a Law may potentially raise problem. The Law concerning general election of DPR, DPD and DPRD members consisting of 320 Articles and 52 Articles regulates criminal acts violation. Whereas the Law concerning the election of President and Vice President consisting of 262 contains only 58 Articles related to criminal acts. By percentage, the calculation of the number of articles regulating the criminal acts in the Law of general election of the members of DPR, DPD DPRD is around 16 percent and in the Law concerning on the election of  president and vice president is around 22 percent. Therefore it is necessary to pay more attention on the urgency of considering the acts classification that is stated as criminal and its implications to the criminal Law enforcement in practical field.Keywords: Criminal acts, General Election, Dispute Settlement